Teacher education and students with disabilities in art class: a program evaluation. Issue 1 (2nd January 2023) - Begeske, Jasmine; Lory, Catharine; David, Marie; Rispoli, Mandy
Abstract: The practice of including students with disabilities in art education has existed longer than efforts to increase access to general academic instruction. However, most teacher education programs do not offer sufficient coursework or field experiences in training pre-service art teachers to teach students with disabilities. To examine how pre-service art teachers are trained to provide inclusive art instruction, semi-structured interviews were conducted with art education faculty and instructors across six institutions in the Midwest of United States and interview data were systematically analyzed at three levels, including within case, cross case, and conversation. Results indicate that while all programs offer a required course related to special education, exposure to students with disabilities in field experiences is limited and collaboration between art teachers and special education teachers or paraprofessionals is not emphasized. Recommendations for strengthening teacher education programs in teaching art to students with disabilities are offered based on study findings.